FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP MINAT NASABAH MENGGUNAKAN UANG ELEKTRONIK (E-MONEY) PADA PT. BANK RAKYAT INDONESIA, Tbk. CABANG PANKKUKANG MAKASSAR - Sudirman Dandu (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
This research aims to study the relationship of the use, usefulness / usefulness, and trust in the interests of using electronic money and to find out the dominant factors that influence the interest in using electronic money. Bank BRI, Tbk, Panakukkang Makassar Branch. The analysis method used in this study is the method of multiple linear regression analysis. The results of the study show the perceptions of usage, usefulness / usefulness, and positive and significant trust in the interests of using electronic money at the BRI Bank Panakukkang Makassar Branch. The variable that played a dominant role in the study was the variable ease of use of electronic money at Bank BRI, Tbk, Makassar Panakukkang Branch